Positive electrode material and preparation method and application thereof

By adopting a positive electrode material with a core-shell structure, the water absorption and performance problems of Prussian white sodium ion positive electrode material are solved, and higher cycle stability and rate performance are achieved.

CN119905558AActive Publication Date: 2025-04-29GUANGDONG BRUNP RECYCLING TECH CO LTD +2
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202510078732.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-17
Publication Date
2025-04-29
Estimated Expiration
2045-01-17

AI Technical Summary

Technical Problem

The Prussian white sodium ion cathode material has strong water absorption and is difficult to treat wastewater, resulting in limited industrialization and poor circulation and rate performance.

Method used

The positive electrode material adopts a core-shell structure, the inner core is manganese ferrocyanide, the intermediate layer is manganese ferrocyanide, and the outer shell is manganese ferrocyanide. The lattice spacing and moisture content of the material are controlled through specific preparation methods.

Benefits of technology

The cycle stability and rate performance of the positive electrode material are improved, the absorption of water molecules is reduced, the water absorption of the material is reduced, and the structural stability and interface stability are enhanced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119905558A_ABST
    Figure CN119905558A_ABST
Patent Text Reader

Abstract

The invention discloses a positive electrode material and a preparation method and application thereof, and belongs to the technical field of sodium ion battery positive electrode materials. The positive electrode material has a core-shell structure, the core is manganese sodium ferrocyanide, and the shell is manganese potassium ferrocyanide; and a manganese ferrocyanide intermediate layer is also arranged between the inner core and the shell. The ion radius of Mn < 2 + > in the middle layer is larger than that of Na < + > in the core, the valence state is higher, the lattice spacing can be reduced, and the effect of supporting the structure is achieved, so that the cycling stability of the material is improved, and meanwhile, the absorption of the material to water molecules is inhibited; k < + > in the shell can provide capacity, the ion radius of K < + > is larger than that of Na < + >, a wide ion transmission channel is provided, the structure is more stable, and the K < + > can play a certain role in reducing the water absorption of the material. Due to the existence of the middle layer and the shell, the structural stability of the positive electrode material in the charge-discharge process is greatly improved, the side reaction of the positive electrode and electrolyte is reduced, and the interface stability, the cycle performance and the rate capability are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of positive electrode materials for sodium ion batteries, and in particular to a positive electrode material and a preparation method and application thereof. Background Art

[0002] As a major category of sodium-ion cathode materials, Prussian white is highly favored due to its simple process and high capacity. However, in recent years, research on Prussian white sodium-ion cathode materials, especially research on industrialization, has been significantly less. The main reason is that Prussian white has strong water absorption and high difficulty in wastewater treatment, which seriously restricts its industrialization process; the sodium-ion battery cycle performance and rate performance prepared by the current Prussian white sodium-ion cathode material are poor.

[0003] In view of this, the present invention is proposed. Summary of the invention

[0004] The object of the present invention is to provide a positive electrode material and a preparation method and application thereof, so as to solve or improve the above technical problems.

[0005] The present invention can be implemented like this:

[0006] In a first aspect, the present invention provides a positive electrode material having a core-shell structure, wherein the core of the core-shell structure is sodium manganese ferrocyanide and the shell is potassium manganese ferrocyanide; and there is also an intermediate layer of manganese ferrocyanide between the core and the shell.

[0007] In an optional embodiment, the positive electrode material also has at least one of the following characteristics:

[0008] Feature 1: The molecular formula of the core is Na x Mn[Fe(CN) 6 ] y , where 1 <x≤2,0.7≤y≤1;

[0009] Feature 2: D of positive electrode material 50 Not less than 2.3 μm, preferably 2.3 μm to 3.0 μm;

[0010] Feature 3: The water content of the positive electrode material does not exceed 0.6wt%.

[0011] In a second aspect, the present invention provides a method for preparing a positive electrode material as described above, comprising the following steps: preparing a sodium manganese ferrocyanide inner core; forming a manganese ferrocyanide middle layer on the surface of the sodium manganese ferrocyanide inner core; and forming a potassium manganese ferrocyanide outer shell on the surface of the manganese ferrocyanide middle layer.

[0012] In an optional embodiment, preparing the sodium manganese ferrocyanide core includes: reacting a sodium ferrocyanide solution, a first soluble manganese salt solution, and a complexing agent solution.

[0013] In an optional embodiment, the preparation of the sodium manganese ferrocyanide core includes at least one of the following features:

[0014] Feature 4: The reaction temperature is 30°C to 90°C;

[0015] Feature 5: The reaction pH is 6 to 9;

[0016] Feature 6: Reaction time is 12h~72h;

[0017] Feature 7: The concentration of the sodium ferrocyanide solution is 0.3 mol / L to 0.6 mol / L, and the concentration of the first soluble manganese salt solution is 0.5 mol / L to 2 mol / L; the molar ratio of the sodium ferrocyanide in the sodium ferrocyanide solution to the first soluble manganese salt in the first soluble manganese salt solution is 0.97:1 to 1.03:1;

[0018] Feature 8: The concentration of the complexing agent solution is 0.002 mol / L to 14 mol / L; the molar ratio of the complexing agent in the complexing agent solution to the first soluble manganese salt in the first soluble manganese salt solution is 0.001:1 to 4:1;

[0019] Feature 9: The complexing agent includes at least one of citric acid, maleic acid, citric acid, ethylenediaminetetraacetic acid, sodium citrate and ammonia water;

[0020] Feature 10: The reaction atmosphere is a protective atmosphere;

[0021] Feature 11: The reaction process is carried out under stirring conditions, preferably, the stirring speed is 200 rpm to 600 rpm.

[0022] In an optional embodiment, preparing the manganese ferrocyanide intermediate layer includes: adding a second soluble manganese salt solution to the material obtained by preparing the sodium manganese ferrocyanide core, mixing and reacting.

[0023] In an optional embodiment, the preparation of the manganese ferrocyanide intermediate layer includes at least one of the following features:

[0024] Feature 12: The amount of the second soluble manganese salt in the second soluble manganese salt solution is 3% to 30% of the amount of the first soluble manganese salt in the first soluble manganese salt solution, and the concentration of the second soluble manganese salt solution is 0.5 mol / L to 2 mol / L;

[0025] Feature 13: The addition time of the second soluble manganese salt solution is 0.25h to 1h.

[0026] In an optional embodiment, preparing the potassium manganese ferrocyanide shell includes: performing solid-liquid separation and washing on the material obtained from preparing the manganese ferrocyanide intermediate layer, slurrying the solid phase obtained after washing with water to obtain Prussian white slurry; mixing and reacting the Prussian white slurry with the potassium ferrocyanide solution.

[0027] In an optional embodiment, preparing the potassium manganese ferrocyanide shell includes at least one of the following features:

[0028] Feature 14: The concentration of potassium ferrocyanide solution is 0.3 mol / L to 0.6 mol / L;

[0029] Feature 15: The amount of potassium ferrocyanide in the potassium ferrocyanide solution is 3% to 30% of the amount of ferrocyanide in the Prussian white slurry;

[0030] Feature 16: The average time that potassium manganese ferrocyanide generated by the reaction stays in the aqueous solution does not exceed 15 minutes.

[0031] In an optional embodiment, preparing the potassium manganese ferrocyanide shell further comprises: continuously discharging the mixed slurry generated by the reaction and spray drying it.

[0032] In an optional embodiment, the liquid feed rate of the spray drying is 5 L / h to 30 L / h, and the main tower temperature of the spray drying is 150° C. to 200° C.

[0033] In an optional embodiment, the volume of the container used for the reaction of the Prussian white slurry and the potassium ferrocyanide solution is 1 / 10 to 1 / 5 of the liquid feed volume per hour of the spray drying.

[0034] In an optional embodiment, the volume of the container is 1L to 3L.

[0035] In an optional embodiment, the container is a container with a stirring function.

[0036] In an optional embodiment, the Prussian white slurry and the potassium ferrocyanide solution are mixed through a three-way pipe with a check valve and then enter the spray dryer; preferably, the three-way pipe is subjected to ultrasonic dispersion.

[0037] In a third aspect, the present invention provides a positive electrode plate, wherein the active material in the positive electrode plate includes the positive electrode material of the aforementioned embodiment.

[0038] In a fourth aspect, the present invention provides a battery comprising the positive electrode sheet of the aforementioned embodiment.

[0039] The beneficial effects of the present invention include:

[0040] In the positive electrode material provided by the present invention, the manganese ferrocyanide intermediate layer can reduce the lattice spacing and play a role in supporting the structure, thereby improving the cycle stability of the material and inhibiting the material from absorbing water molecules; the K in the outer shell of potassium manganese ferrocyanide + Not only can it provide capacity, but also K + The ionic radius is also larger than that of Na + The core has a larger ion transmission channel and a more stable structure, which also plays a certain role in reducing the water absorption of the material. The intermediate layer and the outer shell that exist on the outside of the core can greatly improve the structural stability of the positive electrode material during the charge and discharge process, reduce the side reaction between the positive electrode and the electrolyte, and improve the interface stability, cycle performance and rate performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0041] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required for use in the embodiments are briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present invention and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without creative work.

[0042] Figure 1 is a SEM image of the positive electrode material obtained in Example 1;

[0043] Figure 2 TEM image of the positive electrode material obtained in Example 1;

[0044] Figure 3 This is the SEM image of the positive electrode material obtained in Comparative Example 1. DETAILED DESCRIPTION

[0045] In order to make the purpose, technical scheme and advantages of the embodiments of the present invention clearer, the technical scheme in the embodiments of the present invention will be described clearly and completely below. If the specific conditions are not specified in the embodiments, they are carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be purchased commercially.

[0046] The positive electrode material provided by the present invention and its preparation method and application are described in detail below.

[0047] The invention provides a positive electrode material having a core-shell structure, wherein the core of the core-shell structure is sodium manganese ferrocyanide and the shell is potassium manganese ferrocyanide; and a manganese ferrocyanide intermediate layer is provided between the core and the shell.

[0048] The molecular formula of the above core is Na x Mn[Fe(CN) 6 ] y, where 1 <x≤2,0.7≤y≤1。

[0049] In some optional embodiments, the molar ratio of the inner core, the middle layer and the outer shell can be (54-94): (1-26): (5-45), such as 85:5:20 (i.e. 17:1:4), 90:5:10 (i.e. 19:1:2), 85:10:10 (i.e. 17:2:2), 90:2:16 (i.e. 45:1:8), 85:7:16, 94:3:6 or 70:10:40 (i.e. 7:1:4), etc. In addition, other molar ratios can be set according to actual needs.

[0050] In some optional embodiments, D of the above-mentioned positive electrode material 50 Not less than 2.3 μm, for example, it can be 2.3 μm to 3.0 μm, such as 2.3 μm, 2.5 μm, 2.55 μm, 2.56 μm, 2.58 μm, 2.63 μm, 2.64 μm, 2.66 μm, 2.8 μm or 3.0 μm, etc., and can also be other values ​​within the range of 2.3 μm to 3.0 μm. In some specific embodiments, D of the above-mentioned positive electrode material 50 It is 2.55μm~2.66μm.

[0051] In some optional embodiments, the water content of the positive electrode material does not exceed 0.6wt%, such as 0.05wt%, 0.1wt%, 0.2wt%, 0.3wt%, 0.4wt%, 0.5wt% or 0.6wt%, etc., or other values ​​within the range of not more than 0.6wt%. In some specific embodiments, the water content of the positive electrode material can be 0.3wt% to 0.6wt%.

[0052] In some typical embodiments, the core of the positive electrode material is Na 2 Mn[Fe(CN) 6 ], the middle layer is Mn 2 [Fe(CN) 6 ], the shell is K 2 Mn[Fe(CN) 6 ].

[0053] In the positive electrode material provided by the present invention, the manganese ferrocyanide intermediate layer can reduce the lattice spacing and play a supporting structure role, thereby improving the cycle stability of the material and inhibiting the material from absorbing water molecules. + Not only can it provide capacity, but also K + The ionic radius is also larger than that of Na +The structure is larger, has a wider ion transmission channel, and is more stable, which also plays a certain role in reducing the water absorption of the material. The presence of the above-mentioned intermediate layer and shell greatly improves the structural stability of the positive electrode material during the charge and discharge process, reduces the side reaction between the positive electrode and the electrolyte, and improves the interface stability, cycle performance and rate performance.

[0054] Accordingly, the present invention provides a method for preparing the above-mentioned positive electrode material, comprising the following steps:

[0055] Step S1: preparing sodium manganese ferrocyanide core.

[0056] The preparation of the sodium manganese ferrocyanide core comprises: reacting a sodium ferrocyanide solution, a first soluble manganese salt solution and a complexing agent solution together.

[0057] The above process can be carried out in a reaction kettle, wherein the sodium ferrocyanide solution, the first soluble manganese salt solution and the complexing agent solution are simultaneously introduced into the reaction kettle, and sodium manganese ferrocyanide is synthesized under a certain reaction atmosphere, stirring speed, reaction temperature, reaction pH value and reaction time.

[0058] In some optional embodiments, the reaction temperature can be 30°C to 90°C, such as 30°C, 35°C, 40°C, 45°C, 50°C, 55°C, 60°C, 65°C, 70°C, 75°C, 80°C, 85°C or 90°C, etc., or other values ​​within the range of 30°C to 90°C. In some specific embodiments, the reaction temperature can be 40°C to 90°C.

[0059] The reaction pH value may be 6 to 9, such as 6, 6.5, 7, 7.5, 8, 8.5 or 9, or other values ​​within the range of 6 to 9. In some specific embodiments, the pH value may be 6.6 to 9.0.

[0060] The reaction time can be 12 h to 72 h, such as 12 h, 24 h, 36 h, 48 h, 60 h or 72 h, etc., or other values ​​within the range of 12 h to 72 h.

[0061] In some optional embodiments, the concentration of the sodium ferrocyanide solution can be 0.3mol / L to 0.6mol / L, such as 0.3mol / L, 0.35mol / L, 0.4mol / L, 0.45mol / L, 0.5mol / L, 0.55mol / L or 0.6mol / L, etc., or it can be other values ​​within the range of 0.3mol / L to 0.6mol / L.

[0062] The concentration of the first soluble manganese salt solution can be 0.5mol / L to 2mol / L, such as 0.5mol / L, 0.8mol / L, 1.0mol / L, 1.2mol / L, 1.5mol / L, 1.8mol / L or 2mol / L, etc., or it can be other values ​​within the range of 0.5mol / L to 2mol / L.

[0063] The first soluble manganese salt solution may illustratively be at least one of a manganese sulfate solution, a manganese chloride solution, a manganese nitrate solution and a manganese acetate solution.

[0064] In some optional embodiments, the molar ratio of sodium ferrocyanide in the sodium ferrocyanide solution to the first soluble manganese salt in the first soluble manganese salt solution can be 0.97: 1 to 1.03: 1, such as 0.97: 1, 0.98: 1, 0.99: 1, 1.00: 1, 1.01: 1, 1.02: 1 or 1.03: 1, etc., or other values ​​within the range of 0.97: 1 to 1.03: 1. In some specific embodiments, the molar ratio of sodium ferrocyanide in the sodium ferrocyanide solution to the first soluble manganese salt in the first soluble manganese salt solution can be 1: 1.

[0065] In some optional embodiments, the concentration of the complexing agent solution can be 0.002mol / L to 14mol / L, such as 0.002mol / L, 0.01mol / L, 0.1mol / L, 1mol / L, 2mol / L, 5mol / L, 8mol / L, 10mol / L, 12mol / L or 14mol / L, etc., or it can be other values ​​within the range of 0.002mol / L to 14mol / L.

[0066] The molar ratio of the complexing agent in the complexing agent solution to the first soluble manganese salt in the first soluble manganese salt solution can be 0.001:1 to 4:1, such as 0.001:1, 0.01:1, 0.1:1, 0.5:1, 1:1, 1.5:1, 2:1, 2.5:1, 3:1, 3.5:1 or 4:1, etc., and can also be other values ​​within the range of 0.001:1 to 4:1. In some specific embodiments, the molar ratio of the complexing agent in the complexing agent solution to the first soluble manganese salt in the first soluble manganese salt solution can be 0.5:1 to 2:1.

[0067] The complexing agent may illustratively but not limitatively include at least one of citric acid, maleic acid, citric acid, ethylenediaminetetraacetic acid, sodium citrate and ammonia water.

[0068] In some optional embodiments, the reaction atmosphere in this step is a protective atmosphere, such as nitrogen and / or argon.

[0069] In some optional embodiments, the reaction process of this step is carried out under stirring conditions, wherein the stirring speed can be 200rpm to 600rpm, such as 200rpm, 300rpm, 400rpm, 500rpm or 600rpm, etc., or other values ​​within the range of 200rpm to 600rpm.

[0070] Taking the first soluble manganese salt solution as a manganese sulfate solution as an example, the reaction equation involved in step S1 includes: MnSO 4 +Na 4 Fe(CN) 6 =Na 2 Mn[Fe(CN) 6 ]↓+Na 2 SO 4 .

[0071] The formation of manganese ferrocyanide intermediate layer is due to Mn 2+ To Na + The substitution reaction of Mn 2+ Than Na + The ionic radius is large and the valence state is higher, which can reduce the lattice spacing and play the role of supporting structure, thereby improving the cyclic stability of the material.

[0072] Step S2: forming a manganese ferrocyanide intermediate layer on the surface of the sodium manganese ferrocyanide inner core.

[0073] The preparation of the manganese ferrocyanide intermediate layer comprises: adding a second soluble manganese salt solution to the material obtained by preparing the sodium manganese ferrocyanide core, mixing and reacting.

[0074] In some optional embodiments, the amount of the second soluble manganese salt in the second soluble manganese salt solution is 3% to 30% of the amount of the first soluble manganese salt in the first soluble manganese salt solution, such as 3%, 5%, 10%, 15%, 20%, 25% or 30%, etc., and can also be other values ​​within the range of 3% to 30%.

[0075] The concentration of the second soluble manganese salt solution can be 0.5 mol / L to 2 mol / L, such as 0.5 mol / L, 1 mol / L, 1.5 mol / L or 2 mol / L, or other values ​​within the range of 0.5 mol / L to 2 mol / L.

[0076] The addition time of the second soluble manganese salt solution can be 0.25h to 1h, such as 0.25h, 0.5h, 0.75h or 1h, etc., or other values ​​within the range of 0.25h to 1h.

[0077] In some typical embodiments, the second soluble manganese salt solution and the first soluble manganese salt solution are the same soluble manganese salt solution, for example, both can be manganese sulfate solutions with a concentration of 0.5 mol / L to 2 mol / L.

[0078] Since sodium ferrocyanide has completely reacted with manganese sulfate solution in step S1, in step S2, by continuing to add manganese sulfate solution in a short time (0.25h to 1h), the newly added manganese sulfate solution is actually an excess part compared with sodium ferrocyanide; the excess manganese sulfate solution reacts with the sodium manganese ferrocyanide core generated in step S1 to form manganese ferrocyanide on the surface of the sodium manganese ferrocyanide core, and the reaction equation includes:

[0079] MnSO 4 +Na 2 Mn[Fe(CN) 6 ]=Mn 2 [Fe(CN) 6 ]+Na 2 SO 4 .

[0080] It should be noted that due to the short reaction time, manganese ferrocyanide mainly accumulates on the surface of the sodium manganese ferrocyanide core to form a coating layer, and does not have time to penetrate into the interior of the sodium manganese ferrocyanide core.

[0081] Step S3: forming a potassium manganese ferrocyanide shell on the surface of the manganese ferrocyanide intermediate layer.

[0082] The preparation of potassium manganese ferrocyanide shell includes: performing solid-liquid separation and washing on the material obtained from preparing the manganese ferrocyanide intermediate layer, slurrying the solid phase obtained after washing with water to obtain Prussian white slurry; mixing the Prussian white slurry with potassium ferrocyanide solution and reacting.

[0083] In some optional embodiments, the material obtained by preparing the manganese ferrocyanide intermediate layer is passed to a centrifuge for filtration, then washed to remove impurities, and the filter cake is slurried with water to obtain a Prussian white slurry. Subsequently, the Prussian white slurry and the potassium ferrocyanide solution are continuously introduced into a reaction container, so that the manganese ferrocyanide on the surface of the Prussian white reacts with the potassium ferrocyanide in the potassium ferrocyanide solution to form a manganese potassium ferrocyanide shell.

[0084] The chemical formula of the reaction between the above manganese ferrocyanide and potassium ferrocyanide in the potassium ferrocyanide solution is:

[0085] Mn 2 [Fe(CN) 6 ]+K 4 Fe(CN) 6 =2K 2 Mn[Fe(CN)6 ].

[0086] In some optional embodiments, the concentration of the potassium ferrocyanide solution can be 0.3mol / L to 0.6mol / L, such as 0.3mol / L, 0.4mol / L, 0.5mol / L or 0.6mol / L, etc., or other values ​​within the range of 0.3mol / L to 0.6mol / L.

[0087] In some optional embodiments, the amount of potassium ferrocyanide in the potassium ferrocyanide solution can be 3% to 30% of the amount of ferrocyanide in the Prussian white slurry, such as 3%, 5%, 10%, 15%, 20%, 25% or 30%, etc., or other values ​​within the range of 3% to 30%.

[0088] In some optional embodiments, the average time that potassium manganese ferrocyanide generated by the reaction stays in the aqueous solution does not exceed 15 min, such as 15 min, 12 min, 10 min, 8 min, 5 min, 2 min or 1 min, etc., or other values ​​within the range of not more than 15 min.

[0089] In some optional embodiments, the preparation of potassium manganese ferrocyanide shell further comprises: continuously discharging the mixed slurry generated by the reaction and spray drying the mixed slurry. The spray drying is performed in a spray dryer.

[0090] The liquid feed rate of spray drying can be 5 L / h to 30 L / h, such as 5 L / h, 10 L / h, 15 L / h, 20 L / h, 25 L / h or 30 L / h, or other values ​​within the range of 5 L / h to 30 L / h.

[0091] The temperature of the main tower of the spray drying can be 150°C to 200°C, such as 150°C, 160°C, 170°C, 180°C, 190°C or 200°C, etc., or other values ​​within the range of 150°C to 200°C.

[0092] In some optional embodiments, the volume of the container used for the reaction of Prussian white slurry and potassium ferrocyanide solution can be 1 / 10 to 1 / 5 of the liquid input per hour of spray drying, such as 1 / 10, 1 / 9, 1 / 8, 1 / 7, 1 / 6 or 1 / 5, etc., or other values ​​within the range of 1 / 10 to 1 / 5.

[0093] In some optional embodiments, the volume of the container may be 1L to 3L, such as 1L, 1.5L, 2L, 2.5L or 3L, etc., or may be other values ​​within the range of 1L to 3L.

[0094] In some optional embodiments, the container is a container with a stirring function, such as a stirrer.

[0095] In some optional embodiments, the Prussian white slurry and the potassium ferrocyanide solution are mixed through a three-way pipe with a check valve and then enter the spray dryer. In some more typical embodiments, the three-way pipe can be ultrasonically dispersed to prevent the material from adhering to the pipe wall, thereby shortening the residence time of potassium manganese ferrocyanide in the aqueous solution.

[0096] It should be noted that the mixing of the Prussian white slurry and the potassium ferrocyanide solution in the present invention can include two methods: one is mixing in a stirring tank and then entering the spray dryer through a one-way pipe; the other is directly mixing through a three-way pipe and entering the spray dryer.

[0097] In the above, in step S3, manganese ferrocyanide reacts quickly with potassium ferrocyanide in the potassium ferrocyanide solution to form potassium manganese ferrocyanide quickly without any by-products. If it stays in the aqueous solution for too long, Prussian white will dissolve and recrystallize. + Gradually penetrate into the material and destroy the protective layer. In addition, the volume of the container for synthesizing potassium manganese ferrocyanide should not be too large. The volume of the container should be 1 / 10 to 1 / 5 of the hourly liquid intake of the spray dryer. During the continuous feeding and discharging process, it can not only maintain the continuous occurrence of the reaction, but also ensure that the average time potassium manganese ferrocyanide stays in the aqueous solution does not exceed 15 minutes. By mixing the Prussian white slurry and potassium ferrocyanide solution through a three-way pipe with a check valve and then entering the spray dryer, and ultrasonically dispersing the pipe, the water is quickly evaporated during the spray drying process, reducing the interstitial water content of the material, and the potassium manganese ferrocyanide on the surface of the material is quickly fixed, avoiding K + Penetrates into the material to maintain the integrity of the protective layer.

[0098] The method for preparing the positive electrode material provided by the present invention is simple to operate, low in cost, highly controllable, and suitable for industrial production.

[0099] In addition, the present invention also provides a positive electrode plate, in which the active material includes the positive electrode material mentioned above.

[0100] The present invention also provides a battery cell, which includes the above-mentioned positive electrode plate.

[0101] For example, the battery cells may be used in, but are not limited to, electrical devices such as vehicles, ships or aircraft.

[0102] The present invention also provides a battery comprising the battery monomer.

[0103] The present invention also provides an electric device, which includes the above-mentioned battery cell and / or battery. As an example, the electric device can be, but not limited to, a mobile phone, a tablet, a laptop computer, an electric toy, an electric tool, a battery car, an electric car, a ship, a spacecraft, etc. Among them, the electric toy can include a fixed or mobile electric toy, such as a game console, an electric car toy, an electric ship toy, and an electric airplane toy, etc., and the spacecraft can include an airplane, a rocket, a space shuttle, and a spacecraft, etc.

[0104] The features and performance of the present invention are further described in detail below in conjunction with the embodiments.

[0105] Example 1

[0106] This embodiment provides a positive electrode material, and the preparation method thereof includes:

[0107] Step S1: preparing sodium manganese ferrocyanide core.

[0108] 0.5 mol / L sodium ferrocyanide solution, 2 mol / L manganese sulfate solution and 2 mol / L sodium citrate solution were simultaneously introduced into a reactor, and sodium manganese ferrocyanide was synthesized under the conditions of nitrogen atmosphere, stirring speed of 400 rpm, reaction temperature of 65°C and reaction pH of 8.2. The molar ratio of the total amount of sodium ferrocyanide to manganese sulfate was 1:1, and the molar ratio of the total amount of sodium citrate to manganese sulfate was 2:1. The time for each solution to be introduced into the reactor was 24 hours.

[0109] Step S2: preparing a manganese ferrocyanide intermediate layer.

[0110] To the material obtained in step S1, manganese sulfate solution (concentration of 2 mol / L) was continuously added, the amount of manganese sulfate continuously added was 10% of the amount of manganese sulfate in step S1, and the liquid addition time was 0.3 h, so that manganese ferrocyanide was generated on the surface of sodium manganese ferrocyanide.

[0111] Step S3: preparing potassium manganese ferrocyanide shell.

[0112] The slurry obtained in step S2 is passed to a centrifuge for filtration and washing to remove impurities, and then the filter cake is slurried with water to obtain a Prussian white slurry. The Prussian white slurry is passed into a small stirring tank with a volume of 1L together with a 0.4mol / L potassium ferrocyanide solution. The amount of potassium ferrocyanide used is 5% of the amount of Prussian white ferrocyanide in the Prussian white slurry, so that the manganese ferrocyanide on the surface of the Prussian white reacts with the potassium ferrocyanide in the solution to form a potassium ferrocyanide manganese shell; at the same time, the slurry in the stirring tank is passed into a spray dryer (main tower temperature is 180°C) at a liquid feed rate of 10L / h for drying to obtain a positive electrode material. The average time that the potassium ferrocyanide manganese generated by the reaction stays in the aqueous solution is calculated by the volume of the stirring tank / the liquid feed rate of the spray dryer, that is, 1L / (10L / h)=0.1h=6min.

[0113] The SEM and TEM images of the positive electrode material obtained in this embodiment are shown in Figure 1 and Figure 2 As shown by Figure 1 It can be seen that the positive electrode material has two protective layers, and a small amount of coating can be seen on the surface of the positive electrode material. Figure 2 It can be seen that the positive electrode material has a three-layer structure, including a core, an intermediate layer and an outer shell from the inside to the outside. The intermediate layer and the outer shell are both protective layers. The composition of the core is Na 2 Mn[Fe(CN) 6 ], the composition of the middle layer is Mn 2 [Fe(CN) 6 ], the shell composition is K 2 Mn[Fe(CN) 6 ], the molar ratios of the inner core, the middle layer and the outer shell are 90:5:10 (i.e. 19:1:2) respectively.

[0114] Example 2

[0115] This embodiment provides a positive electrode material, and the preparation method thereof includes:

[0116] Step S1: preparing sodium manganese ferrocyanide core.

[0117] 0.4 mol / L sodium ferrocyanide solution, 2 mol / L manganese sulfate solution and 2 mol / L sodium citrate solution were simultaneously introduced into a reactor, and sodium manganese ferrocyanide was synthesized under the conditions of nitrogen atmosphere, stirring speed of 350 rpm, reaction temperature of 75°C and reaction pH of 8.2. The molar ratio of the total amount of sodium ferrocyanide to manganese sulfate was 1:1, and the molar ratio of the total amount of sodium citrate to manganese sulfate was 1.5:1. The time for each solution to be introduced into the reactor was 40 hours.

[0118] Step S2: preparing a manganese ferrocyanide intermediate layer.

[0119] To the material obtained in step S1, manganese sulfate solution (concentration of 2 mol / L) was continuously added, the amount of manganese sulfate continuously added was 15% of the amount of manganese sulfate in step S1, and the liquid addition time was 0.4 h, so that manganese ferrocyanide was generated on the surface of sodium manganese ferrocyanide.

[0120] Step S3: preparing potassium manganese ferrocyanide shell.

[0121] The slurry obtained in step S2 is passed to a centrifuge for filtration and washing to remove impurities, and then the filter cake is slurried with water to obtain Prussian white slurry. The Prussian white slurry is passed together with a 0.5 mol / L potassium ferrocyanide solution into a small stirring tank with a volume of 1 L, and the amount of potassium ferrocyanide used is 10% of the amount of Prussian white ferrocyanide in the Prussian white slurry, so that the manganese ferrocyanide on the surface of the Prussian white reacts with the potassium ferrocyanide in the solution to form a potassium ferrocyanide manganese shell; at the same time, the slurry in the stirring tank is passed into a spray dryer (main tower temperature is 160°C) at a liquid feed rate of 10 L / h for drying to obtain a positive electrode material.

[0122] The positive electrode material obtained in this embodiment includes a core, an intermediate layer and a shell from the inside to the outside. The composition of the core is Na 2 Mn[Fe(CN) 6 ], the composition of the middle layer is Mn 2 [Fe(CN) 6 ], the shell composition is K 2 Mn[Fe(CN) 6 ], the molar ratios of the inner core, the middle layer and the outer shell are 85:5:20 (i.e. 17:1:4) respectively.

[0123] Example 3

[0124] This embodiment provides a positive electrode material, and the preparation method thereof includes:

[0125] Step S1: preparing sodium manganese ferrocyanide core.

[0126] 0.5 mol / L sodium ferrocyanide solution, 1.6 mol / L manganese sulfate solution and 2 mol / L sodium citrate solution were simultaneously introduced into the reactor, and sodium manganese ferrocyanide was synthesized under the conditions of nitrogen atmosphere, stirring speed of 350 rpm, reaction temperature of 75°C and reaction pH of 8.1. The molar ratio of the total amount of sodium ferrocyanide to manganese sulfate was 1:1, and the molar ratio of the total amount of sodium citrate to manganese sulfate was 1.3:1. The time for each solution to be introduced into the reactor was 48 hours.

[0127] Step S2: preparing a manganese ferrocyanide intermediate layer.

[0128] To the material obtained in step S1, manganese sulfate solution (concentration of 1.6 mol / L) was continuously added, the amount of manganese sulfate continuously added was 15% of the amount of manganese sulfate in step S1, and the liquid addition time was 0.5 h, so that manganese ferrocyanide was generated on the surface of sodium manganese ferrocyanide.

[0129] Step S3: preparing potassium manganese ferrocyanide shell.

[0130] The slurry obtained in step S2 is passed to a centrifuge for filtration and washing to remove impurities, and then the filter cake is slurried with water to obtain Prussian white slurry. The Prussian white slurry is passed together with a 0.4 mol / L potassium ferrocyanide solution into a small stirring tank with a volume of 1L, and the amount of potassium ferrocyanide used is 5% of the amount of Prussian white ferrocyanide in the Prussian white slurry, so that the manganese ferrocyanide on the surface of the Prussian white reacts with the potassium ferrocyanide in the solution to form a potassium ferrocyanide manganese shell; at the same time, the slurry in the stirring tank is passed into a spray dryer (main tower temperature is 180°C) at a liquid feed rate of 10L / h for drying to obtain a positive electrode material.

[0131] The positive electrode material obtained in this embodiment includes a core, an intermediate layer and a shell from the inside to the outside. The composition of the core is Na 2 Mn[Fe(CN) 6 ], the composition of the middle layer is Mn 2 [Fe(CN) 6 ], the shell composition is K 2 Mn[Fe(CN) 6 ], the molar ratios of the inner core, the middle layer and the outer shell are 85:10:10 (i.e. 17:2:2).

[0132] Example 4

[0133] This embodiment provides a positive electrode material, and the preparation method thereof includes:

[0134] Step S1: preparing sodium manganese ferrocyanide core.

[0135] 0.5 mol / L sodium ferrocyanide solution, 2 mol / L manganese sulfate solution and 2 mol / L sodium citrate solution were simultaneously introduced into a reactor, and sodium manganese ferrocyanide was synthesized under the conditions of nitrogen atmosphere, stirring speed of 400 rpm, reaction temperature of 85°C and reaction pH of 8.0. The molar ratio of the total amount of sodium ferrocyanide to manganese sulfate was 1:1, and the molar ratio of the total amount of sodium citrate to manganese sulfate was 2:1. The time for each solution to be introduced into the reactor was 48 hours.

[0136] Step S2: preparing a manganese ferrocyanide intermediate layer.

[0137] To the material obtained in step S1, manganese sulfate solution (concentration of 2 mol / L) was continuously added, the amount of manganese sulfate continuously added was 10% of the amount of manganese sulfate in step S1, and the liquid addition time was 0.5 h, so that manganese ferrocyanide was generated on the surface of sodium manganese ferrocyanide.

[0138] Step S3: preparing potassium manganese ferrocyanide shell.

[0139] The slurry obtained in step S2 is passed to a centrifuge for filtration and washing to remove impurities, and then the filter cake is slurried with water to obtain Prussian white slurry. The Prussian white slurry is passed together with a 0.5 mol / L potassium ferrocyanide solution into a small stirring tank with a volume of 1 L, and the amount of potassium ferrocyanide used is 8% of the amount of Prussian white ferrocyanide in the Prussian white slurry, so that the manganese ferrocyanide on the surface of the Prussian white reacts with the potassium ferrocyanide in the solution to form a potassium ferrocyanide manganese shell; at the same time, the slurry in the stirring tank is passed into a spray dryer (main tower temperature is 180°C) at a liquid feed rate of 10 L / h for drying to obtain a positive electrode material.

[0140] The positive electrode material obtained in this embodiment includes a core, an intermediate layer and a shell from the inside to the outside. The composition of the core is Na 2 Mn[Fe(CN) 6 ], the composition of the middle layer is Mn 2 [Fe(CN) 6 ], the shell composition is K 2 Mn[Fe(CN) 6 ], the molar ratios of the inner core, the middle layer and the outer shell are 90:2:16 (i.e. 45:1:8) respectively.

[0141] Example 5

[0142] This embodiment provides a positive electrode material, and the preparation method thereof includes:

[0143] Step S1: preparing sodium manganese ferrocyanide core.

[0144] 0.5 mol / L sodium ferrocyanide solution, 1.8 mol / L manganese sulfate solution and 2 mol / L sodium citrate solution were simultaneously introduced into a reactor, and sodium manganese ferrocyanide was synthesized under the conditions of nitrogen atmosphere, stirring speed of 400 rpm, reaction temperature of 65°C and reaction pH of 8.3. The molar ratio of the total amount of sodium ferrocyanide to manganese sulfate was 1:1, and the molar ratio of the total amount of sodium citrate to manganese sulfate was 2:1. The time for each solution to be introduced into the reactor was 60 hours.

[0145] Step S2: preparing a manganese ferrocyanide intermediate layer.

[0146] Manganese sulfate solution (concentration of 1.8 mol / L) was continued to be added to the material obtained in step S1, and the amount of manganese sulfate continued to be added was 15% of the amount of manganese sulfate in step S1, and the liquid feeding time was 0.6 h, so that manganese ferrocyanide was generated on the surface of sodium manganese ferrocyanide.

[0147] Step S3: preparing potassium manganese ferrocyanide shell.

[0148] The slurry obtained in step S2 is passed to a centrifuge for filtration and washing to remove impurities, and then the filter cake is slurried with water to obtain Prussian white slurry. The Prussian white slurry is passed together with a 0.5 mol / L potassium ferrocyanide solution into a small stirring tank with a volume of 1 L, and the amount of potassium ferrocyanide used is 8% of the amount of Prussian white ferrocyanide in the Prussian white slurry, so that the manganese ferrocyanide on the surface of the Prussian white reacts with the potassium ferrocyanide in the solution to form a potassium ferrocyanide manganese shell; at the same time, the slurry in the stirring tank is passed into a spray dryer (main tower temperature is 160°C) at a liquid feed rate of 10 L / h for drying to obtain a positive electrode material.

[0149] The positive electrode material obtained in this embodiment includes a core, an intermediate layer and a shell from the inside to the outside. The composition of the core is Na 2 Mn[Fe(CN) 6 ], the composition of the middle layer is Mn 2 [Fe(CN) 6 ], the shell composition is K 2 Mn[Fe(CN) 6 ], the molar ratios of the inner core, the middle layer and the outer shell are 85:7:16 respectively.

[0150] Example 6

[0151] This embodiment provides a positive electrode material, and the preparation method thereof includes:

[0152] Step S1: preparing sodium manganese ferrocyanide core.

[0153] 0.3 mol / L sodium ferrocyanide solution, 0.5 mol / L manganese sulfate solution, 1 mol / L sodium citrate and 0.002 mol / L ethylenediaminetetraacetic acid mixed complexing agent solution were simultaneously introduced into a reactor, and sodium manganese ferrocyanide was synthesized under the conditions of nitrogen atmosphere, stirring speed of 200 rpm, reaction temperature of 90°C and reaction pH of 6.6. The molar ratio of the total amount of sodium ferrocyanide to manganese sulfate was 1:1, and the molar ratio of the total amount of complexing agent to manganese sulfate was 0.5:1. The time for each solution to be introduced into the reactor was 72 hours.

[0154] Step S2: preparing a manganese ferrocyanide intermediate layer.

[0155] To the material obtained in step S1, manganese sulfate solution (concentration of 0.5 mol / L) was continuously added, the amount of manganese sulfate continuously added was 6% of the amount of manganese sulfate in step S1, and the liquid addition time was 0.25 h, so that manganese ferrocyanide was generated on the surface of sodium manganese ferrocyanide.

[0156] Step S3: preparing potassium manganese ferrocyanide shell.

[0157] The slurry obtained in step S2 is passed to a centrifuge for filtration and washing to remove impurities, and then the filter cake is slurried with water to obtain Prussian white slurry. The Prussian white slurry is passed together with a 0.3 mol / L potassium ferrocyanide solution into a small stirring tank with a volume of 1 L, and the amount of potassium ferrocyanide used is 3% of the amount of Prussian white ferrocyanide in the Prussian white slurry, so that the manganese ferrocyanide on the surface of the Prussian white reacts with the potassium ferrocyanide in the solution to form a potassium ferrocyanide manganese shell; at the same time, the slurry in the stirring tank is passed into a spray dryer (main tower temperature is 150°C) at a liquid feed rate of 5 L / h for drying to obtain a positive electrode material.

[0158] The positive electrode material obtained in this embodiment includes a core, an intermediate layer and a shell from the inside to the outside. The composition of the core is Na 2 Mn[Fe(CN) 6 ], the composition of the middle layer is Mn 2 [Fe(CN) 6 ], the shell composition is K 2 Mn[Fe(CN) 6 ], the molar ratios of the inner core, the middle layer and the outer shell are 94:3:6 respectively.

[0159] Example 7

[0160] This embodiment provides a positive electrode material, and the preparation method thereof includes:

[0161] Step S1: preparing sodium manganese ferrocyanide core.

[0162] 0.6 mol / L sodium ferrocyanide solution, 2 mol / L manganese sulfate solution, 3 mol / L sodium citrate and 0.5 mol / L ammonia mixed complexing agent solution were simultaneously introduced into the reactor, and sodium manganese ferrocyanide was synthesized under the conditions of nitrogen atmosphere, stirring speed of 600 rpm, reaction temperature of 40°C and reaction pH of 9.0. The molar ratio of the total amount of sodium ferrocyanide to manganese sulfate was 1:1, and the molar ratio of the total amount of complexing agent to manganese sulfate was 2:1. The time for each solution to be introduced into the reactor was 12 hours.

[0163] Step S2: preparing a manganese ferrocyanide intermediate layer.

[0164] To the material obtained in step S1, manganese sulfate solution (concentration of 2 mol / L) was continuously added, the amount of manganese sulfate continuously added was 30% of the amount of manganese sulfate in step S1, and the liquid addition time was 1 hour, so that manganese ferrocyanide was generated on the surface of sodium manganese ferrocyanide.

[0165] Step S3: preparing potassium manganese ferrocyanide shell.

[0166] The slurry obtained in step S2 is passed to a centrifuge for filtration and washing to remove impurities, and then the filter cake is slurried with water to obtain Prussian white slurry. The Prussian white slurry and a 0.6 mol / L potassium ferrocyanide solution are passed into a small stirring tank with a volume of 3 L, and the amount of potassium ferrocyanide used is 20% of the amount of Prussian white ferrocyanide in the Prussian white slurry, so that the manganese ferrocyanide on the surface of the Prussian white reacts with the potassium ferrocyanide in the solution to form a potassium ferrocyanide manganese shell; at the same time, the slurry in the stirring tank is passed into a spray dryer (main tower temperature is 200°C) at a liquid feed rate of 30 L / h for drying to obtain a positive electrode material.

[0167] The positive electrode material obtained in this embodiment includes a core, an intermediate layer and a shell from the inside to the outside. The composition of the core is Na 2 Mn[Fe(CN) 6 ], the composition of the middle layer is Mn 2 [Fe(CN) 6 ], the shell composition is K 2 Mn[Fe(CN) 6 ], the molar ratios of the inner core, the middle layer and the outer shell are 70:10:40 (i.e. 7:1:4) respectively.

[0168] Example 8

[0169] The difference between this embodiment and embodiment 1 is that in step S3, the Prussian white slurry is mixed with 0.4 mol / L potassium ferrocyanide solution through a three-way pipe with a check valve and ultrasonic dispersion and then immediately enters the spray dryer.

[0170] Comparative Example 1

[0171] After sodium manganese ferrocyanide is synthesized according to step S1 of Example 1, subsequent preparation of the intermediate layer and the outer shell is not performed, and filtering, washing, slurrying, and spray drying are directly performed to obtain the finished product.

[0172] The SEM image of the positive electrode material obtained in this comparative example is as follows Figure 3 As shown by Figure 3 It can be seen that the positive electrode material is composed only of sodium manganese ferrocyanide and has no attachments on the surface.

[0173] Comparative Example 2

[0174] Sodium manganese ferrocyanide was synthesized and coated with manganese ferrocyanide according to step S1 and step S2 of Example 1, and the finished product was directly obtained by filtering, washing, slurrying and spray drying without preparing the subsequent potassium manganese ferrocyanide shell.

[0175] In the positive electrode material, Na 2 Mn[Fe(CN) 6 ] and Mn 2 [Fe(CN) 6 ] has a molar ratio of 9:1.

[0176] Comparative Example 3

[0177] The difference between this comparative example and Example 1 is that no intermediate layer is provided, and the positive electrode material is composed of a sodium manganese ferrocyanide inner core and a potassium manganese ferrohydride outer shell in a molar ratio of 19:2.

[0178] Comparative Example 4

[0179] The difference between this comparative example and Example 1 is that in step S2, the second soluble manganese salt solution is added for 0.1 h.

[0180] Comparative Example 5

[0181] The difference between this comparative example and Example 1 is that in step S2, the second soluble manganese salt solution is added for 2 hours.

[0182] Comparative Example 6

[0183] The difference between this comparative example and Example 1 is that in step S3, the average time that potassium manganese ferrocyanide generated by the reaction stays in the aqueous solution is 20 minutes.

[0184] Comparative Example 7

[0185] The difference between this comparative example and Example 1 is that in step S3, the volume of the reaction container (stirring tank) is 1 / 2 of the hourly liquid intake of the spray dryer.

[0186] Comparative Example 8

[0187] The difference between this comparative example and Example 1 is that in step S3, the potassium manganese ferrocyanide generated by the reaction is not continuously discharged and spray-dried, but the material is discharged and spray-dried after the reaction is completely completed.

[0188] Test example

[0189] ①, the particle size D of the positive electrode materials obtained in Examples 1 to 8 and Comparative Examples 1 to 8 50 And the moisture content is tested. Among them, the particle size D 50 The test was carried out using a Malvern particle size analyzer and the moisture content was tested using an automatic moisture tester. The results are shown in Table 1.

[0190] ②, the positive electrode materials obtained in Examples 1 to 8 and Comparative Examples 1 to 8 were respectively prepared into positive electrode sheets, with metallic sodium as the negative electrode, NaPF 6 The ethylene carbonate (EC) / diethyl carbonate (DEC) solution was used as the electrolyte and assembled into a button half-cell in a glove box. Then, the charge and discharge were performed at 0.1C and 5C rates in the voltage range of 2.0V to 4.0V, and the cycle was performed at 0.1C for 500 cycles. The discharge specific capacity and capacity retention rate are shown in Table 1. The physical and chemical parameters of the positive electrode material are shown in Table 1.

[0191] Table 1 Data of Examples and Comparative Examples

[0192]

[0193] It can be seen from Table 1 that Comparative Example 1 is pure sodium manganese ferrocyanide, which has the highest water content, the worst 5C discharge specific capacity, and the capacity retention rate after 500 cycles at 0.1C is also low.

[0194] In Comparative Example 2, a layer of manganese ferrocyanide is coated on the surface of sodium manganese ferrocyanide. Compared with Comparative Example 1, the water content of Comparative Example 2 is reduced, and the 0.1C discharge specific capacity is slightly reduced, but the 5C discharge specific capacity and the capacity retention rate of 0.1C cycle 500 cycles are improved, indicating that the coating of manganese ferrocyanide has a certain improvement effect on the rate performance and cycle performance, but will sacrifice a little capacity.

[0195] Examples 1 to 8 were all double-coated. Compared with Comparative Example 1, the particle size was not much different, but the moisture content of the material was greatly reduced. The 0.1C discharge capacity was almost unchanged compared with Comparative Example 1, and the 5C discharge capacity was significantly improved. After 500 cycles at 0.1C, the capacity retention rate was significantly improved. Compared with Comparative Example 2, Examples 1 to 8 had lower moisture content and higher capacity, indicating that the potassium manganese ferrocyanide on the surface played a role in reducing moisture content and increasing capacity.

[0196] Combining the results of Examples 1 to 8 and Comparative Examples 1 to 3, it can be seen that the three-layer structure of Prussian white has better cycle performance and rate performance.

[0197] In addition, it can be seen from the comparison between Example 1 and Comparative Example 3 that Comparative Example 3 has no intermediate layer, has a relatively high water content, and has slightly poor 5C discharge specific capacity and 0.1C cycle 500 cycle capacity retention rate.

[0198] From the comparison between Example 1 and Comparative Examples 4-5, it can be seen that the liquid injection time of S2 has a certain influence on the discharge specific capacity and capacity retention rate of the material. Too short or too long liquid injection time is not conducive to the stability and permeability of the intermediate layer, causing the electrical performance to deteriorate.

[0199] From the comparison between Example 1 and Comparative Examples 6 to 8, it can be seen that the average residence time of potassium manganese ferrocyanide in the aqueous solution should not be too long, and the faster the spray drying is performed, the better. The longer the time, the more potassium ions penetrate into the material, and the greater the destructive effect on the rate performance (discharge specific capacity).

[0200] In summary, the positive electrode material provided by the present invention has poor water absorption and a stable structure during the charge and discharge process, which is beneficial to reduce the side reaction between the positive electrode and the electrolyte and improve the interface stability, cycle performance and rate performance of the battery.

[0201] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A positive electrode material, characterized in that: The positive electrode material has a core-shell structure, wherein the core of the core-shell structure is sodium manganese ferrocyanide and the shell is potassium manganese ferrocyanide; and an intermediate layer of manganese ferrocyanide is provided between the core and the shell.

2. The positive electrode material according to claim 1, characterized in that The positive electrode material also has at least one of the following characteristics: Feature 1: The molecular formula of the core is Na x Mn[Fe(CN)6] y , where 1 <x≤2,0.7≤y≤1; Feature 2: D of the positive electrode material 50 Not less than 2.3 μm, preferably 2.3 μm to 3.0 μm; Feature 3: The water content of the positive electrode material does not exceed 0.6wt%.

3. A method for preparing a positive electrode material as claimed in claim 1 or 2, characterized in that: The following steps are involved: A sodium manganese ferrocyanide inner core is prepared; a manganese ferrocyanide middle layer is formed on the surface of the sodium manganese ferrocyanide inner core; and a potassium manganese ferrocyanide outer shell is formed on the surface of the manganese ferrocyanide middle layer.

4. The preparation method according to claim 3, characterized in that: The preparation of the sodium manganese ferrocyanide core comprises: reacting a sodium ferrocyanide solution, a first soluble manganese salt solution and a complexing agent solution together.

5. The preparation method according to claim 4, characterized in that: The preparation of the sodium manganese ferrocyanide core includes at least one of the following features: Feature 4: The reaction temperature is 30°C to 90°C; Feature 5: The reaction pH is 6 to 9; Feature 6: Reaction time is 12h to 72h; Feature 7: The concentration of the sodium ferrocyanide solution is 0.3 mol / L to 0.6 mol / L, and the concentration of the first soluble manganese salt solution is 0.5 mol / L to 2 mol / L; the molar ratio of sodium ferrocyanide in the sodium ferrocyanide solution to the first soluble manganese salt in the first soluble manganese salt solution is 0.97:1 to 1.03:1; Feature 8: The concentration of the complexing agent solution is 0.002 mol / L to 14 mol / L; the molar ratio of the complexing agent in the complexing agent solution to the first soluble manganese salt in the first soluble manganese salt solution is 0.001:1 to 4:1; Feature 9: The complexing agent includes at least one of citric acid, maleic acid, citric acid, ethylenediaminetetraacetic acid, sodium citrate and ammonia water; Feature 10: The reaction atmosphere is a protective atmosphere; Feature 11: The reaction process is carried out under stirring conditions, preferably, the stirring speed is 200 rpm to 600 rpm.

6. The preparation method according to claim 4 or 5, characterized in that: The preparation of the manganese ferrocyanide intermediate layer comprises: adding a second soluble manganese salt solution to the material obtained by preparing the manganese sodium ferrocyanide core, mixing and reacting; Preferably, the preparation of the manganese ferrocyanide intermediate layer includes at least one of the following features: Feature 12: The amount of the second soluble manganese salt in the second soluble manganese salt solution is 3% to 30% of the amount of the first soluble manganese salt in the first soluble manganese salt solution, and the concentration of the second soluble manganese salt solution is 0.5 mol / L to 2 mol / L; Feature 13: The addition time of the second soluble manganese salt solution is 0.25h to 1h.

7. The preparation method according to claim 6, characterized in that: The preparation of potassium manganese ferrocyanide shell comprises: performing solid-liquid separation and washing on the material obtained by preparing the manganese ferrocyanide intermediate layer, slurrying the solid phase obtained after washing with water to obtain Prussian white slurry; mixing the Prussian white slurry with potassium ferrocyanide solution and reacting; Preferably, the preparation of the potassium manganese ferrocyanide shell includes at least one of the following features: Feature 14: The concentration of the potassium ferrocyanide solution is 0.3 mol / L to 0.6 mol / L; Feature 15: The amount of potassium ferrocyanide in the potassium ferrocyanide solution is 3% to 30% of the amount of ferrocyanide in the Prussian white slurry; Feature 16: The average time that potassium manganese ferrocyanide generated by the reaction stays in the aqueous solution does not exceed 15 minutes.

8. The preparation method according to claim 7, characterized in that: The method for preparing potassium manganese ferrocyanide shell further comprises: continuously discharging the mixed slurry generated by the reaction and spray drying the mixed slurry; Preferably, the liquid feed rate of the spray drying is 5L / h to 30L / h, and the main tower temperature of the spray drying is 150°C to 200°C; Preferably, the volume of the container used for the reaction of the Prussian white slurry and the potassium ferrocyanide solution is 1 / 10 to 1 / 5 of the liquid feed volume per hour of the spray drying; Preferably, the volume of the container is 1L to 3L; Preferably, the container is a container with a stirring function; Preferably, the Prussian white slurry and potassium ferrocyanide solution are mixed through a three-way pipe with a check valve and then enter the spray dryer; more preferably, the three-way pipe is subjected to ultrasonic dispersion.

9. A positive electrode sheet, characterized in that: The active material in the positive electrode sheet includes the positive electrode material according to claim 1 or 2.

10. A battery, characterized in that: The battery comprises the positive electrode sheet according to claim 9.

Citation Information

Patent Citations

  • Low-water low-defect ferrocyanide manganese potassium Prussian blue cubic crystal and preparation method thereof

    CN110002466A

  • Prussian blue positive electrode material with multilayer structure and preparation method and application thereof

    CN114497472A

  • Prussian blue composite positive electrode material, preparation method thereof and sodium ion battery

    CN116093286A

  • Prussian blue sodium ion battery positive electrode material, preparation method and sodium battery

    CN116525795A

  • Pre-lithiated silica material, preparation method and application thereof, and lithium ion battery

    CN117476904A